The Process of Claiming Asset in Bahagian Pembahagian Pusaka (BPP) - Muhammad Naqiyuddin Ismail; Norhazlina Ibrahim; Safeza Mohd Sapian (HRMARS, 2024)
International Journal of Academic Research in Business and Social Sciences Vol: 13, Issue: 12 (page: 3456-3465)